Transport and InsP8 gating mechanisms of the human inorganic phosphate exporter XPR1 - Qinyu Zhu; Madeleine F. Yaggi; Nikolaus Jork; Henning J. Jessen; Melinda M. Diver (Nature Communications)
Abstract Inorganic phosphate (Pi) has essential metabolic and structural roles in living organisms. The Pi exporter, XPR1/SLC53A1, is critical for cellular Pi homeostasis. When intercellular Pi is high, cells accumulate inositol pyrophosphate (1,5-InsP8), a signaling molecule required for XPR1 function. Inactivating XPR1 mutations lead to brain calcifications, causing neurological symptoms including movement disorders, psychosis, and dementia. Here, cryo-electron microscopy structures of dimeric XPR1 and functional characterization delineate the substrate translocation pathway and how InsP8 initiates Pi transport. Binding of InsP8 to XPR1, but not the related inositol polyphosphate InsP6, rigidifies the intracellular SPX domains, with InsP8 bridging the dimers and SPX and transmembrane domains. Locked in this state, the C-terminal tail is sequestered, revealing the entrance to the transport pathway, thus explaining the obligate roles of the SPX domain and InsP8. Together, these findings advance our understanding of XPR1 transport activity and expand opportunities for rationalizing disease mechanisms and therapeutic intervention.